CFD Simulation of Two-Phase Flow in Rectangular Conduit - Kamaruddin, Siti Maryam (IRC, 2018)
The slug flow regime is an unsteady nature which cause problems in the transportation of the fluid through a pipeline. Thus, slugging is very undesirable in the pipeline, and it is commonly happened in circular pipe since circular pipe is widely used in transporting two-phase flow of fluid compared to other geometrical shape. Concurrently, the used of other geometrical shape especially rectangular duct is very uncommon in petroleum industrial application make the investigation on slug flow in rectangular duct is necessary. The objective of this study is to investigate water-gas slug flow in rectangular conduit by comparing numerical result with circular pipe having the same cross-sectional area. The transition of fluid flow pattern in the pipe is due to significant change in liquid or gas velocities. Thus, Volume of Fluid (VOF) method in ANSYS FLUENT 16.1 software was used to capture the transient distribution of gas and liquid interface throughout the pipe. The simulation of the model is simulated using the same parameters as recent numerical data in horizontal circular pipe. This is to make sure the result of the simulation can be compared meticulously with circular pipe having the same cross-sectional area. Finally, analyses on substantial region of slug flow regime for water-gas two-phase flow in two different geometrical shape were carried out.